-3(-3x+9)=0

Simple and best practice solution for -3(-3x+9)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3(-3x+9)=0 equation:



-3(-3x+9)=0
We multiply parentheses
9x-27=0
We move all terms containing x to the left, all other terms to the right
9x=27
x=27/9
x=3

See similar equations:

| 20=x3 | | 82°=(10x-8) | | -10x+51=10x+51 | | 3=27-5y | | 3x-15=-5x+12 | | 4x+17=3x+ | | 36+8x=4x+4 | | .5789+b=7 | | 8x+8=32x | | 1/3=x/x6 | | 3/4(2x-6)=-6 | | x^2=3.06 | | 3x=14.7 | | 15=-2y+5 | | c/16=8 | | x-x(0.13)=30000 | | 13=w+24 | | 9m-1=-1-6m-m | | (x)=5/7 | | (g+6)+12=4 | | 26=8+9f | | h/4+25=33 | | 7(y-5=14 | | h÷4+25=33 | | m+14=-24 | | v+3=21 | | h«4+25=33 | | 1(-12x-3)+9=-9(x+5)+33 | | g-18=-7 | | 4b-9b=35 | | {c}{8}=98c=9 | | {c}{8}=98c​ =9 |

Equations solver categories